Organizational socialization is an mediator to the effect of Plateaus and workaholism in employees loyalty - الخفاجي, رشا مهدي (Journal of Economics and Administrative Sciences, 2018)
The research aimed to test the effect of independent variables career plateaus and workaholism on employees loyalty through the influence of the mediator variable organizational socialization. Descriptive approach with survey style   on a sample of managers and executives in the Iraqi Drilling Company in Basra's (123) employees. The most important findings of the research are: the existence of a significant effect of the independent variables career plateaus and workaholism in employees loyalty by having a mediator variable organizational socialization and introduced numerical from recommendations.